NA K-EDGE XANES SPECTRA OF MINERALS AND GLASSES - Neuville D.R.; Cormier L.; Flank A.-M.; Lagarde P.; Prado R.J. (My University, 2004)
Na K-edge X ray absorption near-edge structure (XANES) spectra for minerals and glasses were collected using synchrotron radiation. Na-K XANES is a good structural probe to determine the coordination state of this element in important minerals and glasses. From the XANES spectra on crystalline reference phases with different chemical environment, information can be obtained and compared with the structure of the minerals and glasses. The different classes of studied minerals correspond to distinct Na K-edge spectra which have been examined. The XANES spectra for the crystalline references are used as fingerprint to interpret those obtained on silicate and borate glasses. Experimental spectra for jadeite and carnegieite crystals can be satisfactorily reproduced by theoretical calculations using the Full Multiple Scattering formalism.